ANALISIS IMPLEMENTASI PROMOSI K3 DALAM UPAYA PENCEGAHAN KECELAKAAN KERJA DI PT X (PROYEK PEMBANGUNAN GEDUNG Y SEMARANG) - Nurhuda Destari; Baju Widjasena; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The construction sector is the highest contributor to the number of occupational accidents in Indonesia, it is quoted on the website of the Ministry of Public Works. Eighty five percent of the causes of accidents is the contribution of unsafe work behavior. Occupational accidents are still found in PT X is like falls, scratched, crushed, pierced by nails and falling objects. One of accidents and illness prevention due to work done by carrying out occupational safety and health promotion. The purpose of this study was to analyze the implementation of occupational safety and health promotion in preventing occupational accidents in PT X building project Y Semarang. The method of this research was qualitative research with in-depth interview and observational approach. The subjects of this study were 3 people as key informants and 3 for informants triangulation. The results showed safety health and environment policy has written, dated, and approved by the Director. Budgeting system for occupational safety and health promotion program has been budgeted in the form of draft Budget. Occupational safety and health promotion procedures has written only for the safety morning program, while for other promotional programs there has been no written procedures. Facilities and infrastructure necessary to support the implementation of occupational safety and health promotion is already available in the form of loudspeakers and place of execution. The conclusion from this research is PT X building projects Y Semarang already implemented promotional programs such as safety morning, safety induction, toolbox meetings, installation of signs and safety posters. However, the implementation of the program had not maximized.